2015
DOI: 10.1016/j.jpeds.2015.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Variants in Solute Carrier SLC26A9 Modify Prenatal Exocrine Pancreatic Damage in Cystic Fibrosis

Abstract: Objectives To test the hypothesis that multiple constituents of the apical plasma membrane residing alongside the causal CF Transmembrane Conductance Regulator (CFTR) protein, including known cystic fibrosis (CF) modifiers SLC26A9, SLC6A14, and SLC9A3, would be associated with prenatal exocrine pancreatic damage as measured by newborn screened (NBS) IRT levels. Study design NBS IRT measures and genome-wide genotype data were available on 111 subjects from Colorado, 37 subjects from Wisconsin, and 80 subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 40 publications
0
51
0
Order By: Relevance
“…These results support a role of SLC26A9 as an alternative chloride channel that may contribute to the regulation of airway surface liquid (ASL) essential for mucus clearance under pathophysiological conditions. Third, data emerging from genetic studies in humans provide independent evidence supporting the role of SLC26A9 as a disease modifier in CF and potentially other chronic obstructive lung diseases [83][84][85][86][87]. Specifically, consistent with a protective function of SLC26A9 in Th2-mediated airway inflammation, it was shown that a functional SNP (rs2282430) is associated with asthma in children [83].…”
Section: Slc26a9mentioning
confidence: 85%
See 1 more Smart Citation
“…These results support a role of SLC26A9 as an alternative chloride channel that may contribute to the regulation of airway surface liquid (ASL) essential for mucus clearance under pathophysiological conditions. Third, data emerging from genetic studies in humans provide independent evidence supporting the role of SLC26A9 as a disease modifier in CF and potentially other chronic obstructive lung diseases [83][84][85][86][87]. Specifically, consistent with a protective function of SLC26A9 in Th2-mediated airway inflammation, it was shown that a functional SNP (rs2282430) is associated with asthma in children [83].…”
Section: Slc26a9mentioning
confidence: 85%
“…Interestingly, some of these variants were recently detected in patients with CF-like lung disease [85]. Further, SLC26A9 polymorphisms were also found to be associated with the risk to develop meconium ileus and early exocrine pancreatic disease in patients with CF [86,87].…”
Section: Slc26a9mentioning
confidence: 97%
“…Furthermore, it is known that variants (SNPs) in the SLC26A9 anion transporter can influence disease severity in the CF lungs and gut (meconium ileus) and, therefore, act as gene modifiers. Importantly, a recent study has suggested that SNPs in SLC26A9 can also influence the degree of pancreatic insufficiency [181]. This opens up the possibility of targeting this anion transporter as a potential therapeutic target to slow the progression of exocrine dysfunction in CF (in addition to the lungs and ileum).…”
Section: Role Of Cftr In the Exocrine Pancreasmentioning
confidence: 99%
“…These variants, and others with similar strength of evidence, are located in a cluster just 5′ or in intron 1 of SLC26A9 in a region where few variants favor OR = 1 as a plausible value demarcating the associated region. Rs7512462 in intron 5 and rs4077468 have been demonstrated in previous P‐ value based studies as associated with CF pancreatic disease (Blackman et al, ; Miller et al, ) and therapeutic response (Strug et al, ).…”
Section: Genetic Analysis With the Epmentioning
confidence: 83%
“…Individuals with CF who have the same CFTR mutations have variable disease severity, and other genes referred to as modifier genes contribute to this interindividual variation (Cutting, 2015). One modifier gene locus, encompassing SLC26A9, was identified through genome-wide association studies to contribute to CF intestinal and pancreatic disease (Miller et al, 2015;Sun et al, 2012;Blackman et al, 2013). The functional role of SLC26A9 is not completely understood, although several studies suggest, like CFTR, SLC26A9 is an anion channel that may enhance the functional expression of CFTR through physical interaction (Loriol et al, 2008;Ohana, Yang, Shcheynikov, & Muallem, 2009).…”
Section: The Epmentioning
confidence: 99%